22.5k views
2 votes
Given that the first term is LaTeX: t_1=2t 1 = 2, and the recursive definition is LaTeX: t_{n+1}=3^{\left(t_n\right)}t n + 1 = 3 ( t n ), what would be the 2nd term (LaTeX: t_2t 2).

Given that the first term is LaTeX: t_1=2t 1 = 2, and the recursive definition is-example-1
User Axois
by
5.7k points

2 Answers

4 votes

Answer:

the correct answer is 9

Explanation:

took the test and it was correct

User Tigt
by
5.5k points
5 votes

*100% CORRECT ANSWERS

Given that the first term is LaTeX: t_1=2t 1 = 2, and the recursive definition is-example-1
Given that the first term is LaTeX: t_1=2t 1 = 2, and the recursive definition is-example-2
Given that the first term is LaTeX: t_1=2t 1 = 2, and the recursive definition is-example-3
User Sander Declerck
by
4.9k points